High-Quality Development Evaluation of Cultural and Tourism Integration Empowered by the Digital Economy under Double Valued Neutrosophic Sets - Jun Wang; Xiong Hu (Neutrosophic Sets and Systems)
This study proposed a decision-making approach to evaluate the cultural and tourism integration empowered by the digital economy. Two methods are used in this study, such as Entropy method to compute the criteria weights and the MABAC method to rank the alternatives. These methods are used under the neutrosophic sets. Neutrosophic sets (NSs) are used to represent ambiguous, inconsistent, and unpredictable data that arise in practical issues. Indeterminacy leaning toward truth membership and indeterminacy leaning toward falsity membership are two separate components of double-valued neutrosophic sets (DVNSs), a variant of NSs. Three experts have evaluated the criteria and alternatives. Ten criteria and six alternatives are used in this study. We show the Digital Infrastructure criterion has the highest weight.